Marketing Strategy Implementation: A Study of Small and Medium Companies in Indonesia - Asmai Ishak (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
A good marketing strategy does not always necessarily lead to successful marketing performance in an organization. It depends on how marketing people translate the strategy into action. A well formulated, but badly implemented strategy, will be effective (do the right things), but not efficient (do things right). While correct implementation of a badly formulated strategy will be efficient, but not effective. Firms need both effectiveness and efficiency to optimize their performance. This study, based on existing literature, identified a list of activities concerning the marketing strategy implementation, and investigated their nature in the process of the strategy implementation among small and medium companies in Indonesia. A tested structured questionnaire was used as a guidance in interviewing marketing managers -the respondents of the study. A total of 76 completed questionnaires were collected. Factor analysis was used to extract, if any, key dimensions across the data. This analysis resulted into four fundamental factors underlying 16 activities in marketing strategy implementation, namely commitment, consensus, evaluation and control, autonomy, and two factors representing 8 marketing performance that are financial, and strategic performances. Subsequently simple regression was performed to examine the impact of the four factors on the marketing performance. The study findings suggest that evaluation and control has greatest impact either on financial performance or strategic performance, followed by autonomy. Even though commitment and consensus influence the marketing performance, but their influences are not statistically significant.